2010
DOI: 10.1136/jech.2009.100651
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differentials in cause-specific mortality among 1.4 million South Korean public servants and their dependents

Abstract: Graded inverse associations between income and mortality were found for most, but not all, specific causes of death. The major contributors to income differentials in total mortality in men were liver disease (15.4%), stroke (12.8%), land transport accidents (10.0%), lung cancer (7.1%) and liver cancer (7.0%). In women, stroke (30.7%), diabetes (9.1%), land transport accidents (6.6%), liver cancer (6.0%) and liver disease (5.1%) were important. Conclusions The contribution of the cause of death to socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Therefore, prior studies in Korea have used insurance premium levels as an SEP indicator 28, 29. For this reason, the current study also used SEP criteria created using insurance premiums of the National Health Insurance System.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, prior studies in Korea have used insurance premium levels as an SEP indicator 28, 29. For this reason, the current study also used SEP criteria created using insurance premiums of the National Health Insurance System.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported the contribution of causes of death in specific age groups to socioeconomic mortality inequalities in Asia as well as in western countries [1-5]. They revealed that the pattern of the contribution by specific causes of death varied by countries, which informs of different policy priorities for different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the contribution of causes of death to total inequalities in mortality can suggest a basis for specific intervention points. However, there are few studies that shed light on this topic [13]. Although a recent report did assess the contribution of causes of death to mortality inequalities in Korea, the study could neither include the entire Korean population nor address long-term tendencies [13].…”
Section: Introductionmentioning
confidence: 99%